Knowledge Creation in Life Sciences Scientific Research Teams: A Qualitative Study of Principal Investigators in Lithuania - Taparauskienė, Simona; Jokūbauskienė, Saulė (Information & Media, 2025)
Knowledge creation in research teams is a continuous process. Scientists representing different fields collaborate in interdisciplinary teams, as combining knowledge from various fields enables them to solve complex scientific problems. Europe’s digital decade, the European Union’s Artificial Intelligence Regulation 2024/1689, is expected to shape the global labor market by 2030, driven by the interplay of geoeconomic fragmentation, knowledge-economy uncertainty, and sustainability. It is essential to emphasize that breakthrough technology at a national level can be developed by small groups of scientists. Information and communication technologies are crucial for ensuring the storage and transfer of data, information, and knowledge, both within teams and between teams. The study employs a semi-structured qualitative interview method to examine the knowledge-creation process in scientific research teams in the life sciences. Based on a literature review and qualitative research, the study finds that the knowledge-creation process in those teams aligns with the knowledge conversion model. The methods used for knowledge creation include conducting experiments, taking laboratory notes, reflecting, engaging in scientific discussions, patenting, reading and writing scientific articles, and searching for information in databases. The cultivation of organizational culture and the use of information and communication technology tools are two criteria that support an effective knowledge-creation process.